2020
DOI: 10.25259/sni_593_2019
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic cervical spine injury: Short-and medium-term prognostic factors in 102 patients

Abstract: Background: Traumatic cervical spine injuries (CSIs) can be defined as osteodiscoligamentous lesions and are frequent in the young and active population. These lesions are often associated with significant devastating neurological deficits. Here, we sought to establish short-and medium-term prognostic factors that could help predict future outcomes. Methods: We retrospectively reviewed 102 adults admitted for traumatic CSI over an 11-year period (January 2004–December 2014). Patients were graded using Franke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In severe injuries, the edema and hematoma can appear and increase in the first 48 hours and decrease gradually in the next three weeks, while hematoma indicates that Asia grade in the patient is A, or B, or some patients with C grade [ 23 ]. Grade A and B and neurodegenerative disorders at admission affect the prognosis [ 24 ]. Whatever is fractured type affected the C1-C2 stability.…”
Section: Discussionmentioning
confidence: 99%
“…In severe injuries, the edema and hematoma can appear and increase in the first 48 hours and decrease gradually in the next three weeks, while hematoma indicates that Asia grade in the patient is A, or B, or some patients with C grade [ 23 ]. Grade A and B and neurodegenerative disorders at admission affect the prognosis [ 24 ]. Whatever is fractured type affected the C1-C2 stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, in pediatric patients, complications such as 30% of screw pulling out in suboccipital area, 10.4% of other complications rate including vertebral artery injuries and mortality rate of up to 9% after complex spine decompression and fixation should be taken into consideration [20] [26] [27] [28] [29]. Abboud et al reported worse Frankel grade (A or B) and neurovegetative disorders at presentation to be strongly statistically correlated with poor prognosis factor and higher mortality in 102 cases of cervical spine trauma over a study period of 11 years [4] [10] [30]. Despite the existence of those both latter factors in one of our patients (Case 1), his condition improved dramatically, moving from ASIA A with neurovegetative disorders preoperatively, to ASIA E postoperatively without any symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…S urgical management of cervical spine trauma carries a high risk of complications and mortality. [1][2][3][4] Various studies have reported on the mortality rate for patients with cervical spine injuries, which may be as high as 79%. 1,5,6 A variety of factors may influence perioperative mortality, and there is a need for appropriate risk stratification.…”
mentioning
confidence: 99%
“…Surgical management of cervical spine trauma carries a high risk of complications and mortality 1–4 . Various studies have reported on the mortality rate for patients with cervical spine injuries, which may be as high as 79% 1,5,6 .…”
mentioning
confidence: 99%